2021
DOI: 10.1021/acsami.1c01217
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance Assessment of Low-Pressure Affinity Membranes Based on Functionalized, Electrospun Polyacrylates for Gold Nanoparticle Filtration

Abstract: Electrospun nanofibrous membranes (ENM) possess many advantages over commonly utilized water purification systems. They provide high porosity with interconnected pores and a high surface to volume ratio, facilitating particle adsorption. Affinity separation moves into a promising future for application, for example, nanoparticle adsorption with excellent filtration efficiency, because of its highly specific adsorption mechanism. However, not all effects on filtration performance are entirely understood. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Procedures for copolymerization, electrospinning, cross-linking, as well as membrane properties were already published in our previous paper. 44 Scanning electron microscopy (SEM) images of membranes are visualized in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedures for copolymerization, electrospinning, cross-linking, as well as membrane properties were already published in our previous paper. 44 Scanning electron microscopy (SEM) images of membranes are visualized in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The membrane properties, such as fiber diameter, pore size, tensile strength, and pressure drop were investigated. Procedures for copolymerization, electrospinning, cross-linking, as well as membrane properties were already published in our previous paper . Scanning electron microscopy (SEM) images of membranes are visualized in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26658-88-8) was used. A number-average molecular weight of 100 000 was determined by gel permeation chromatography as described elsewhere using N , N -dimethylformamide (DMF) as the eluent and narrowly distributed polystyrene standards for calibration.…”
Section: Methodsmentioning
confidence: 99%
“…The Pyr mechanism was based on physical adsorption while the Nplus mechanism was based on attraction of particles by ionic charge (chemical adsorption). It was further concluded that the pressure drop studies were controlled mostly by the pore size and tensile strength of the nanofiber membranes [164] Flux decline was also reduced during the filtration of Acid Orange 7 [91]. Gao et al enhanced the photocatalytic performance of a filtration membrane in both UV and visible light irradiation through surface modification using TiO 2 -GO nanocomposites.…”
Section: Filtrationmentioning
confidence: 99%